2016
DOI: 10.1097/yco.0000000000000244
|View full text |Cite
|
Sign up to set email alerts
|

Gamma band oscillations

Abstract: Purpose of review We review our current understanding of abnormal γ band oscillations in schizophrenia, their association with symptoms and the underlying cortical circuit abnormality, with a particular focus on the role of fast-spiking parvalbumin gamma-aminobutyric acid (GABA) neurons in the disease state. Recent findings Clinical electrophysiological studies of schizophrenia patients and pharmacological models of the disorder show an increase in spontaneous γ band activity (not stimulus-evoked) measures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
70
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(72 citation statements)
references
References 90 publications
2
70
0
Order By: Relevance
“…Another strategy is to explore medicines that ameliorate dysfunctional GABAergic neurons. The latter strategy is based on the concept that the hypofunction of NMDA receptors located on GABAergic neurons leads to the attenuated activity of GABAergic neurons, and this, in turn, produces abnormal gamma oscillations and cognitive deficits in schizophrenia patients ( 113 ).…”
Section: A Direction Of Novel Therapeuticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another strategy is to explore medicines that ameliorate dysfunctional GABAergic neurons. The latter strategy is based on the concept that the hypofunction of NMDA receptors located on GABAergic neurons leads to the attenuated activity of GABAergic neurons, and this, in turn, produces abnormal gamma oscillations and cognitive deficits in schizophrenia patients ( 113 ).…”
Section: A Direction Of Novel Therapeuticsmentioning
confidence: 99%
“…Furthermore, Nakamura et al ( 120 ) reported that the oral administration of T-817MA ameliorated behavioral, histological, and neurophysiological changes, such as deficits in prepulse inhibition, reduced levels of parvalbumin-immunoreactive neurons in the medial prefrontal cortex, hippocampus, and amygdala, and a deficit in the auditory phase-locked gamma oscillation in a mouse model of schizophrenia. The modulation of gamma band activity is noteworthy, because abnormal gamma band activity is thought to underlie the psychosis and cognitive deficits, and is considered a target for potential therapeutic interventions ( 113 ).…”
Section: A Direction Of Novel Therapeuticsmentioning
confidence: 99%
“…However, these findings have not translated to better treatments for those with schizophrenia. The three primary symptom groups, positive, cognitive and negative (Box 1 ), have been associated with reports of abnormalities in virtually every neurotransmitter system 1 – 5 . The onset of psychotic symptoms, which is strongly associated with alterations in dopamine function, is a key feature underpinning a clinical diagnosis 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…In many subjects with schizophrenia, PFC PV neurons have 1) lower transcript and protein levels of PV and of a key GABA-synthesizing enzyme, GAD67 (Lewis et al, 2012; Mitchell et al, 2015), 2) compromised integrity of perineuronal nets (PNNs) which regulate structural and synaptic functions (Berretta et al, 2015; Enwright et al, 2016), and 3) lower density of excitatory inputs onto their somata (Chung et al, 2016a). These molecular and structural alterations are thought to impair GABA neurotransmission and to contribute to the lower power of PFC gamma oscillations seen in individuals with schizophrenia (McNally and McCarley, 2016). Indeed, in vivo studies indicate that measures of extracellular GABA, which more closely approximate synaptic GABA than do measures of total GABA levels, are lower in subjects with schizophrenia (Frankle et al, 2015).…”
mentioning
confidence: 99%